Hermite-Hadamard Type Inequalities for Operator $h$-Preinvex Functions (Communications in Mathematical Research, 2019)
Operator $h$-preinvex functions are introduced and a refinement of Hermite-Hadamard type inequalities for such functions is established. Results proved in this paper are more general and some known results are special cases.